Probiotic Use in Childhood - Merve Usta; Nafiye Urgancı (Güncel Pediatri, 2014)
Probiotics are live microorganisms that produce a benefit to host by improving microbial balance in the gut, when provided in adequate amounts from food and supplements. Probiotics, taken with foods or food supplements are bacteria or yeasts. They act by reducing the number of pathogens and harmful bacteria, by changing microbial metabolism and by improving the immune system. They are in capsule, tablet, cachet or powdered form. In randomised controlled trials with probiotics, the prevention of acute infectious diarrhea in healthy infants and children had shown moderate benefits. The effect of probiotics in acute viral diarrhea is well studied. More research is needed to determine the effect of probiotics in antibiotic associated diarrhea, irritable bowel syndrome, ulcerative colitis, Crohn’s disease, helicobacter pylori infection, constipation and extraintestinal infections. There are positive results with probiotics in atopic diseases and preventing necrotising enterocolitis in premature infants. Studies continue for the effectiveness of the probiotics in various clinical conditions in children.